Oxide surface modification: Synthesis and characterization of zirconia-coated alumina - Dalmaschio, Cleocir José; Mastelaro, Valmor Roberto; Nascente, Pedro Augusto de Paula; Bettini, Jeferson; Zotin, José Luiz; Silva, Elson Longo da [UNESP]; Leite, Edson Roberto (Elsevier, 2010)
Four aluminas were used as supports for impregnation with a zirconium oxide with the aim to achieve a coating, without phase separation, between support and modifier. The supports were impregnated with different concentrations of zirconium aqueous resin, obtained through the polymeric precursor method. After impregnation the samples were calcined and then characterized by XRD, which led to identification of crystalline zirconia in different concentrations from each support used. Using a simple geometric model the maximum amount of surface modifier oxide required for the complete coating of a support with a layer of unit cells was estimated. According to this estimate, only the support should be identified below the limit proposed and crystalline zirconium oxide should be identified above this limit when a complete coating is reached. The results obtained from XRD agree with the estimated values and to con- firm the coating, the samples were also characterized by EDS/STEM, HRTEM, XPS, and XAS. The results showed that the zirconium oxide on the surface of alumina support reached the coating in the limit of 15 Zr nm2 , without the formation of the ZrO2 phase.
Keywords: surface; coating; dispersion; Catalysts; ceramics